Las prácticas de laboratorio de física en el desarrollo del aprendizaje significativo de los estudiantes de primero de bachillerato general unificado de la Unidad Educativa Quisapincha, cantón Ambato, provincia de Tungurahua. - Asqui Calero, Asqui Calero (2017)
The research entitled: The laboratory practices of Physics in the development of meaningful learning of the students of the First General Bachillerato Unified of the Educational Unit Quisapincha, Canton Ambato, province of Tungurahua, aims to guide the use of the physical laboratory in activities of kinematics, principles of dynamics and static equilibrium. It is based on philosophical, epistemological, pedagogical, psychological and legal aspects; the theoretical framework focuses on the independent variable that are the laboratory practices with their conceptualizations, principles, advantages, importance and the curriculum; the dependent variable corresponds to the development of meaningful learning referring to its phases, previous knowledge and zone of proximal development. The methodology focuses on a descriptive-explanatory, causal and field research, quasi-experimental and qualitative design, the hypothetical deductive and descriptive method was applied, the technique is the observation supported in the observation sheet. Regarding the alternative guideline, a didactic guide with physics activities concerning kinematics, principles of dynamics and static equilibrium, supported by theoretical and practical processes using the instruments of the physics laboratory, is proposed. With the data of the observation to the students, statistical tables and graphs were elaborated to be analyzed and interpreted according to the percentage, finally the verification of the hypotheses was realized and to define conclusions and recommendations. With the management of the physics laboratory the students developed their cognitive and intellectual capacities because through research and experimentation they found solutions concerning solid bodies, location of an object according to occupation in space, understanding of Newton's laws, an object according to position in space and potential energy.